The Green Flaneur and the Widi2019;d Street Paul Guzzardo (Global Journal of Human-Social Science, 2021)
This excerpt opens Swimming in a Sea of Death A Son s Memoir The author is David Rieff the son of Susan Sontag Nothing could have been further from my mind I thought that I was returning to my home in New York at the end of a long trip abroad Instead I was at the beginning of the journey that would end with my mother s death To be specific it was the afternoon of March 28 2004 a Sunday and I was in Heathrow Airport in London on my way back from the Middle East I began making phone calls reconnecting with home as has always been my habit once I am through reporting a story That was when my mother Susan Sontag told me that there was a chance that she was ill again My mother was clearly doing her best to be cheerful There may be something wrong she finally told me after I had gone on at far too great length about what the West Bank had been like While I had been away she said she had gone in for her twice-yearly scans and blood tests the regular routine that she had been following since her surgery and subsequent chemotherapy for the uterine sarcoma she had been diagnosed with six years earlier One of the blood tests they ve just run doesn t seem so good she said adding that she had already had some further tests done and asking me if I would come with her the following day to see a specialist who had been recommended to her and who had done some follow-up tests a couple of days earlier He would have the conclusive results then